2007
DOI: 10.1002/ldr.836
|View full text |Cite
|
Sign up to set email alerts
|

Modelling spatial uncertainty of soil erodibility factor using joint stochastic simulation

Abstract: Soil erosion varies greatly over space and is commonly estimated using the revised universal soil loss equation (RUSLE). Neglecting information about estimation uncertainty, however, may lead to improper decision-making. One geostatistical approach to spatial analysis is joint stochastic simulation, which draws alternative, equally probable, joint realizations of a regionalized variable. Differences between the realizations provide a measure of spatial uncertainty and allow us to carry out an error propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…On the contrary, Wang et al [92] found improvement in the state of erosion risk in the Danjiangkou reservoir area, China, where the eroded areas have declined from 32.1% in 2004 to 25.43% in the 2010 study period. Moreover, Jiang et al [16] reported that the eroded area has Therefore, since there is geospatial variation in soil erosion risk distribution across the watershed area, identification of priority area is the key factor for planning and implementing appropriate SWC [10][11][12][13][14][15][16][17][18][19]51,90,142]. Accordingly, we prioritized areas with a higher and increasing soil loss rate as SWC priority areas (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Wang et al [92] found improvement in the state of erosion risk in the Danjiangkou reservoir area, China, where the eroded areas have declined from 32.1% in 2004 to 25.43% in the 2010 study period. Moreover, Jiang et al [16] reported that the eroded area has Therefore, since there is geospatial variation in soil erosion risk distribution across the watershed area, identification of priority area is the key factor for planning and implementing appropriate SWC [10][11][12][13][14][15][16][17][18][19]51,90,142]. Accordingly, we prioritized areas with a higher and increasing soil loss rate as SWC priority areas (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches are regarded as "probabilistic" because they explicitly recognize the uncertainty associated with the prediction and assess such uncertainty by the analysis on a set of stochastic simulations (Castrignanò and Buttafuoco 2004;He et al 2010). The statistical quantities, as derived from a series of equally probable realizations, allow uncertainty to be assessed and then the consequences of data uncertainty on decision making evaluated (Castrignanò et al 2008;Barca and Passarella 2008). The last decade has witnessed an increasing awareness of the importance of assessing the uncertainty about the value of soil properties at unsampled locations (Grunwald et al 2004;Diodato 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Kriging-based estimators are exact interpolators that provide best, unbiased, linear estimation of the variables by minimizing the estimation variance. With respect to the geostatistical simulation methods, which consider global statistics more than local accuracy, have been developed largely in direct response to the inadequate measures of spatial uncertainty or finite data (Goovaerts 1999;Castrignanò et al 2008). In this study, apparent electrical conductivity was measured in a fairly quick manner by the mobile EMI system and geostatistical simulation methods were not considered.…”
Section: Statistical Prediction Methodsmentioning
confidence: 99%